Analysis of Student Disruptive Behavior in Elementary Schools - Masrurah, Ummie; Fauziati, Endang; Darsinah, D; Wulandari, Murfiah Dewi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The aim of the research is to analyze destructive behavior. Methodology: Type of research qualitative approach. The research method used is a case study. Data collection techniques in this research are observation, documentation and interviews. Data collection in the form of non-test instruments includes documentary research in the form of observations and interviews, as well as counseling guidance data from class teachers and religious teachers as a consultation tool. The data analysis technique used in this research is from the data analysis technique of the Miles and Huberman interaction model (including data reduction, data display, and data validation). The validity of the data was checked using technical triangulation. Using various data collection techniques, namely interviews, observation and documentation. Results: The results of research on disruptive behavior include: students behaving casually, often leaving class, walking around in class, lying on the floor, making noise, fighting, not obeying school rules, neglecting assignments, bullying friends, saying dirty words, throwing objects. at school, talking out of turn, disobeying teacher orders, calling friends by their parents' names, talking to friends during class, physically insulting. The factors that cause disruptive behavior are as follows, the first factor is the family, the second factor is the environment, the third factor is the school environment, the fourth factor is internal to the students. Applications/Originality/Value: Teacher strategies for overcoming disruptive behavior through counseling, collaborating with parents and psychologists, restitution approaches and modeling. In this research, a teacher modeling strategy was developed.